Self-efficacy and academic procrastination of university students in Metropolitan Lima - Alegre, Alberto A. (2013)
The aim of this investigation is establish the relation between self-efficacy and academic procrastination of university students in Lima City metropolitan area. The sample was obtained by intentional procedure. Assessments were made on 348 university students: 50.6% male and 49% female students; 70.1% from private and 29.9% from state universities. Self-Efficacy Scale and Academic Procrastination Scale were used for assessment and it was found they had both psychometric reliability according to internal consistency method and construct validity according to exploratory factorial analysis. The formulated hypothesis is accepted as the correlation coefficient obtained between both variables was negative (-235) and significant (p˂.000) but low.